A Conceptual Contract Framework For Research To Develop A Contract Framework For Outsourcing Of Facilities Management In Malaysian Hospitals - Baba, Maizan; Mohammed, Abdul Hakim (2008)

(untitled)
This paper aims to identify the contract framework for outsourcing of facilities management of hospitals in Malaysia. The scope is the facilities engineering management services. The focus is the operation stage of the outsourcing project. It comprises the service start-up, implementation, on-going service development, review and project close. The framework is identified from the practices of public and private hospitals in Malaysia, and literatures. The public hospitals use a more comprehensive contract due to the big number of hospitals involved, scattered all over the country. There are those that have existed for more than 50 years. The comprehensiveness is to enable the client and consultant to manage, and the contractors and sub-contractors to deliver the large number hospitals specific required service levels. The private hospitals use a simpler contract, as the consultant is a subsidiary company. It stresses the contractors and consultant to follow the practice and procedures of the hospitals. However, both hospitals and the literatures describe the service start-up and implementation processes in more detail than the other three processes. This may imply that both processes have more issues to be managed; there are also more characteristics of requirements for good outsourcing contracts.